Estimation of direct laser acceleration in laser wakefield accelerators using particle-in-cell simulations. (9th February 2016) - Shaw, J L; Lemos, N; Marsh, K A; Tsung, F S; Mori, W B; Joshi, C
Abstract: Many current laser wakefield acceleration (LWFA) experiments are carried out in a regime where the laser pulse length is on the order of or longer than the wake wavelength and where ionization injection is employed to inject electrons into the wake. In these experiments, the electrons can gain a significant amount of energy from the direct laser acceleration (DLA) mechanism as well as the usual LWFA mechanism. Particle-in-cell (PIC) codes are frequently used to discern the relative contribution of these two mechanisms. However, if the longitudinal resolution used in the PIC simulations is inadequate, it can produce numerical heating that can overestimate the transverse motion, which is important in determining the energy gain due to DLA. We have therefore carried out a systematic study of this LWFA regime by varying the longitudinal resolution of PIC simulations and then examining the energy gain characteristics of both the highest-energy electrons and the bulk electrons. By calculating the contribution of DLA to the final energies of the electrons produced from the LWFA, we find that even at the highest longitudinal resolutions, DLA contributes a significant portion of the energy gained by the highest-energy electrons and also contributes to accelerating the bulk of the charge in the electron beam produced by the LWFA.